Brain and cognitive functions in two groups of naïve HIV patients selected for a different plan of antiretroviral therapy: A qEEG study. Issue 11 (November 2016) - Babiloni, Claudio; Pennica, Alfredo; Capotosto, Paolo; Onorati, Paolo; Muratori, Chiara; Ferracuti, Stefano; Roma, Paolo; Correr, Valentina; Piccinni, Elisa; Noce, Giuseppe; Del Percio, Claudio; Cordone, Susanna; et al.
Highlights: In two groups of naïve HIV subjects, 5-months antiretroviral therapy (cART) improves EEG cortical source activity. Improved EEG cortical sources were associated with normalized serum virus load and CD4 cells. In groups of naïve HIV subjects, EEG cortical sources might be useful study endpoints of cART. Abstract: Objective: Cortical sources of electroencephalographic (EEG) rhythms were investigated in two sub-populations of naïve HIV subjects, grouped based on clinical criteria to receive different combination anti-retroviral therapies (cARTs). These EEG sources were hypothesized to reflect beneficial effects of both regimes. Methods: Eyes-closed resting state EEG data were collected in 19 (Group A) and 39 (Group B) naïve HIV subjects at baseline (i.e. pre-treatment; T0) and after 5 months of cART (T5). Compared with the Group A, the Group B was characterized by slightly worse serological parameters and higher cardiovascular risk. At T0, mean viral load (VL) and CD4 count were 87, 694 copies/ml and 435 cells/μl in the Group A and 187, 370 copies/ml and 331 cells/μl in the Group B. The EEG data were also collected in 50 matched control HIV-negative subjects. Cortical EEG sources were assessed by LORETA software. Results: Compared to the Control Group, the HIV Groups showed lower alpha (8–12 Hz) source activity at T0 while the Group B also exhibited higher delta source activity. The treatment partially normalized alpha and delta source activity in the Group A and B, respectively, in association with improved VL, CD4, and cognitive functions. Conclusions: Different cART regimens induced diverse beneficial effects in delta or alpha source activity in the two naïve HIV Groups. Significance: These sources might unveil different neurophysiological effects of diverse cART on brain function in naïve HIV Groups as a function of clinical status and/or therapeutic compounds.